If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -23 = 77 Reorder the terms: -23 + 10x = 77 Solving -23 + 10x = 77 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + 10x = 77 + 23 Combine like terms: -23 + 23 = 0 0 + 10x = 77 + 23 10x = 77 + 23 Combine like terms: 77 + 23 = 100 10x = 100 Divide each side by '10'. x = 10 Simplifying x = 10
| 2(3x+4)=2(4x+1) | | 4x^3+15x^2+37x+39=0 | | 3-2k=-9 | | 8v-10=105 | | (x+1)(x-7)=0 | | 8r^2-12r=0 | | 0=-16x^2+3x+1.3 | | 3x^2+34x+80=0 | | 18=3(d-1) | | 3-4(x+2)=15 | | x^3+x^2-x-1.7=0 | | 3a-32=-2a+23 | | 7(-6y+9)+4y=-13 | | (x*x)+(x*x)=36 | | 137-4x=23x+23 | | 20.4-2c=5 | | 4x+y+1=-y-2x+3 | | (a-b)(a^2+2ab+b^2)= | | 12y^2+2y=0 | | (2c-d)(2c^2+2cd+d^2)= | | 7-7x=29-21x | | 3x+10+x+2=2x+20 | | -3x+7=28 | | 3x-45=6 | | 7(n+6)+8(n+4)= | | 8(x+3)+14(x+2)=74 | | 3(6z-1)-4(z+9)=4(z+1) | | 0.02-2.6=5.38 | | p=3a+5b | | 4x-12=x+6 | | 5b*6b= | | 3x*5x*2x= |